2014
DOI: 10.1039/c4cp00111g
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy studies of dopant activation and free electron density of In0.53Ga0.47As via sulfur monolayer doping

Abstract: We present a Raman spectroscopy study of electron-phonon coupling in In0.53Ga0.47As epilayers doped via the sulfur-monolayer doping method. A high-frequency coupled mode (HFCM) detected above 400 cm(-1) shifts with increasing charge carrier density and allows for extraction of the activated dopant concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Our sub-10 nm n-In 0.53 Ga 0.47 As junctions also possess similar active carrier concentration of $1.5 Â 10 19 À1.7 Â 10 19 cm À3 . The N and t obtained are similar to that reported by Kort et al 24 Furthermore, the corresponding s values appear to fall on the line extrapolated from the thicker reference samples. R s obtained from electrical measurements using the micro-four-point-probe (l4PP) setup and TLM structures are compared with that obtained from infrared ellipsometry measurements in Fig.…”
supporting
confidence: 88%
“…Our sub-10 nm n-In 0.53 Ga 0.47 As junctions also possess similar active carrier concentration of $1.5 Â 10 19 À1.7 Â 10 19 cm À3 . The N and t obtained are similar to that reported by Kort et al 24 Furthermore, the corresponding s values appear to fall on the line extrapolated from the thicker reference samples. R s obtained from electrical measurements using the micro-four-point-probe (l4PP) setup and TLM structures are compared with that obtained from infrared ellipsometry measurements in Fig.…”
supporting
confidence: 88%
“…12 More recent work has shown that it is possible to study the doping concentration in InGaAs using calibrated Raman spectroscopy and the goal of this work is to similarly apply calibrated Raman spectroscopy to investigate the activation of implanted Si in InAs. [13][14][15] EXPERIMENTAL Commercially available, 500 lm thick, 3 in. Zn-doped InAs wafers with a background p-type concentration of 3 Â 10 17 cm À3 grown using the liquid encapsulated Czochralski process were implanted with 20 keV, Si þ over a range of doses from 1 Â 10 13 to -1 Â 10 15 cm À2 at a 7 tilt and 25 rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have used Raman scattering to measure free carrier concentrations making use of the fact that LO phonons will readily couple with the plasma oscillations of free carriers in InAs and other polar, III-V materials. 13,14,[21][22][23][24][25][26][27] The L þ phonon-plasmon coupled mode is especially sensitive to changes in the carrier concentration at high n-type carrier concentrations in InAs where Raman shifts towards higher wavenumbers correspond to increasing free electron concentrations. Diffusion of Si in InAs beyond the initial implanted profile may increase the active sheet number measured by Hall effect precluding accurate carrier concentration estimates without corresponding Si diffusion data.…”
Section: Introductionmentioning
confidence: 99%
“…[53] The process showed an interesting application of Raman and may prove promising as a method to probe dopant incorporation within shallow junctions formed using the 35 MLD technique. D'Costa and co-workers utilised infrared spectroscopic ellipsometry to study S-MLD doped InGaAs ultra-shallow junctions.…”
Section: Monolayer Doping On Gementioning
confidence: 99%